VICTIMS OF THREAT OR VIOLENCE AGAINST A LAW ENFORCEMENT OFFICER: PROSPECTS OF EXPANDING THE LIST OF PERSONS (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to the analysis of the "relatives" category, the outline of the prospects for its implementation in the Criminal Code of Ukraine, in particular, to supplement the list of victims of crimes against the authority of state authorities in the field of law enforcement, namely: threats or violence against a law enforcement officer (art. 345 of the Criminal Code of Ukraine) and several other articles. It is substantiated that this will solve some problems related to the legal qualification of an act committed by a person and ensure an effective investigation of criminal offenses provided for in Art. 345 of the Criminal Code of Ukraine. It is also determined that the outlined changes will ensure proper protection by state institutions of law enforcement officers and military personnel, especially during a full-scale invasion of the territory of our state, when this has become extremely urgent.
Keywords: criminal offense; threat; violence, law enforcement officer; close relatives; close person